Intervening and reducing sharing of false cancer treatments on social media: Online experiment - Allison J. Lazard; Shelby Lake; Tara Licciardello Queen; Mirian Avendaño-Galdamez; Scott Babwah Brennen; Tushar Varma; Hung-Jui Tan; Marjory Charlot; Nabarun Dasgupta (PLoS ONE, 2026)
Background Cancer treatment misinformation (e.g., false cures) is shared widely on social media and harmful. Cancer treatment misinformation is potentially shared because people want to help or provide hope for those with cancer. We need strategies, like prompts that inform others that a post may be false, to redirect individuals to prosocially intervene instead of sharing to reduce cancer treatment misinformation. Objective We examined whether social cue prompts with a post review policy would lead to more intervening and less sharing of cancer treatment misinformation. Methods We conducted a between-persons online experiment with adult participants from the US recruited via Prolific. Participants were randomized to view cancer treatment misinformation social media posts with social cue prompts and a flagging policy (treatment) or no prompts or policy (control) and reported willingness for intervening (e.g., flagging), sharing, and message reactions. Participants also reported their motivations for intervening or sharing the posts. Results Social cue prompts and policies for platform action encouraged participants to intervene (e.g., flag) significantly more than people who did not see prompts, p < .001. Social cue prompts and policies also led to significantly less sharing and sharing actions on social media (e.g., liking posts), p < .001. Social cue prompts (vs. no prompts) led to greater motivation to intervene with the misinformation, most often because it could be false (accuracy concerns) and potentially harmful to people with cancer (empathic concerns), both p < .001. Social cue prompts also led to less motivation to share; fewer would share because the post was interesting or may provide hope (altruistic motivations), both p < .001. Conclusion Prompts (also called warnings, nudges, or labels) on cancer treatment misinformation are a promising approach to encourage intervening (flagging) and reduce sharing on social media. Social cue prompts and policies also reduced common motivations for sharing – to help and provide (false) hope – that could be interpreted as misguided altruism.